Epizootic effect and aftermath in a pilot whale population. Issue 5 (29th April 2019) - Verborgh, Philippe; Gauffier, Pauline; Brévart, Clémentine; Giménez, Joan; Esteban, Ruth; Carbou, Morgane; Debons, Elodie; de Stephanis, Renaud
Abstract: Over the last three decades, emerging infectious diseases have resulted in large mortalities in wild populations. Different strains of Morbillivirus have infected cetaceans all over the world and caused at least seven epizootics since the 1980s, but few data exist on their effect at the population level. The demographic effect of a morbillivirus epizootic was studied on a well‐monitored resident population of long‐finned pilot whales in the Strait of Gibraltar. Results show decreases in population size and apparent survival rate, especially in males, as well as negative population growth rates during the epizootic and the following years. Although different anthropogenic and natural factors may have acted in conjunction, the epizootic was most likely the cause of this observed decline. This epizootic, and potential future ones, may put the population's future at even greater risk, and their habitat is threatened by increasing anthropogenic stress.